Sosialisasi Standar Pelayanan Ekowisata Berbasis Kearifan Lokal untuk Pengelola Wisata di Tepian Sungai Musi Palembang - Muhammad Iqbal; Nyanyu Ully Auliana; M Bambang Purwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This socialization activity aims to increase the understanding of tourism managers on the banks of the Musi River in Palembang regarding ecotourism service standards based on local wisdom. The material presented included the basic concept of sustainable ecotourism, tourism service standards, the application of local wisdom in service, and case studies of the successful implementation of local culture-based ecotourism. The implementation method consists of seminars, interactive training, and group discussions that involve direct simulations in the application of tourism services. The evaluation was carried out through pre-test and post-test which showed a significant improvement in the understanding of participants after participating in the activity. Monitoring is carried out by observing the active participation of participants during the activity. The results of the activity showed that participants were able to understand the importance of implementing ecotourism service standards by prioritizing local wisdom as the main attraction. This activity has a positive impact in improving the quality of tourism services in the area. The resulting recommendations include the need for further assistance activities to ensure sustainable implementation and capacity building for tourism managers in a sustainable manner.